2018
DOI: 10.2217/hep-2017-0021
|View full text |Cite
|
Sign up to set email alerts
|

Development of shellfish allergy after exposure to dual immune checkpoint blockade

Abstract: Hepatocellular carcinoma (HCC) is a major health problem worldwide with limited systemic therapies available. Immunotherapy is a fast-moving field that is quickly evolving as a treatment for HCC with three recent clinical trials published treating HCC with immune checkpoint inhibitors with promising results. Checkpoint inhibition may lead to a unique adverse event profile with the potential to cause immunerelated adverse events by unbalancing the immune system. Here, we report a case of a 61-year-old male with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…This included 11 clinical trials (4 randomized and 7 nonrandomized) and 8 cohort studies (Table 1), 12 case series, and 32 case reports (supplemental online Table 3). Fifty of the articles described the use of immunotherapy agents in the setting of unresectable HCC [13, 14, 18, 29–75], 3 in the neoadjuvant setting [76–78], and 10 in the setting of LT [79–88], and they reported on 2,402 patients in total (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This included 11 clinical trials (4 randomized and 7 nonrandomized) and 8 cohort studies (Table 1), 12 case series, and 32 case reports (supplemental online Table 3). Fifty of the articles described the use of immunotherapy agents in the setting of unresectable HCC [13, 14, 18, 29–75], 3 in the neoadjuvant setting [76–78], and 10 in the setting of LT [79–88], and they reported on 2,402 patients in total (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…The mean score of the NHBLI scale for the case series [31, 32, 37, 39, 40, 44, 51, 62, 67, 77, 80, 84] was 6.8 ± 0.9 (supplemental online Table 6). The mean score of the JBI scale for the case reports [29, 33, 34, 38, 41, 43, 46–50, 52, 55, 61, 64, 65, 68, 69, 71, 72, 74–76, 78, 79, 81–83, 85–88] was 7.2 ± 1.1 (supplemental online Table 7). These results highlight that the included studies were of high quality on average.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, there are several case reports showing the unpredictable and infrequent severe side effects with different outcomes, such as atezolizumab‐induced encephalitis, 34,35 hypopituitarism, 36 polymyalgia rheumatica, 37 adrenocorticotropic hormone deficiency, hypothyroidism and myopathy 38 myocarditis, 39 psoriasiform eruption, 40 autoimmune diabetes mellitus, Takotsubo cardiomyopathy, 41 small bowel perforation, 42 Evans' syndrome, 43 duodenal variceal rupture, 44 liver abscess, 45 thrombotic microangiopathy and mesangial proliferative glomerulonephritis during atezolizumab and bevacizumab treatment 46 . Case reports are scanty in the case of tremelimumab and durvalumab and only a shellfish allergy after treatment has been described but there is less available data due to the late incorporation 47 . These reports emphasize the urgency of identifying tools that assess the risk and severity of developing irAE and their implications for patient outcomes before starting treatment.…”
Section: Swot Analysis Of Systemic Treatment In Hcc Fieldmentioning
confidence: 99%
“…46 Case reports are scanty in the case of tremelimumab and durvalumab and only a shellfish allergy after treatment has been described but there is less available data due to the late incorporation. 47 These reports emphasize the urgency of identifying tools that assess the risk and severity of developing irAE and their implications for patient outcomes before starting treatment. In this regard, Xin et al 48 identified polymorphisms associated with irAEs and irAEs-free survival in PD-1/PD-L1 blockade-treated patients with different types of cancer, but only two patients had HCC in that cohort.…”
Section: Variable Patient Outcomementioning
confidence: 99%